Studies of genetic linkage between adult polycystic kidney disease and three markers on chromosome 16. Issue 8 (August 1987) - Watson, M L; Wright, A F; Macnicol, A M; Allan, P L; Clayton, J F; Dempster, M; Jeremiah, S J; Corney, G; Hopkinson, D A
Abstract : Adult polycystic kidney disease (APKD) is a common genetic disorder that is inherited as an autosomal dominant trait. Recent reports show that, in some families, the APKD gene shows close genetic linkage to two chromosome 16 specific genetic markers. We have been conducting a genetic linkage study using 29 polymorphic isoenzyme and antigenic markers in 184 members of 12 APKD families. We present here the results of linkage analysis using three of these markers which have also been reported to be located on chromosome 16: phosphoglycolate phosphatase (PGP), glutamate pyruvate transaminase (GPT), and haptoglobin (HP). The results show that APKD is closely linked to the PGP locus on the short arm of chromosome 16 (16p13—-p12), which is consistent with the previously reported linkage both to PGP and to the alpha globin locus. The genetic distance between PGP and APKD shows a maximum likelihood value of the recombination fraction at zero with a lod score of 5 X 5. There is no evidence of linkage between APKD and either GPT or HP. The PGP polymorphism potentially provides a useful predictive test to complement the use of alpha globin probes in genetic counselling. These tests should provide an efficient means of primary screening of family members at risk, as well as introducing the possibility of prenatal diagnosis.